2006
DOI: 10.1111/j.1478-3231.2006.01321.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth inhibitory effects of pegylated IFN α‐2b on human liver cancer cells in vitro and in vivo

Abstract: Continuous contact with PEG-IFN-alpha2b induces strong antitumor effects and the down-regulation of IFNAR-2 in HCC cells. The data suggest potential clinical application of PEG-IFN-alpha2b for the prevention and treatment of HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 44 publications
3
34
0
Order By: Relevance
“…Several reports showed that PEG- IFN exhibited a strong anti-tumor effect, and that the combination of PEG-IFN and chemoreagents was effective for the treatment of several cancer types (10,21,22). It was also reported that PEG-IFN had an anti-tumor effect against HCC (11), and our results supported this. In our study, the anti-tumor effect of PEG-IFN was almost the same as that of conventional IFN.…”
Section: Discussionsupporting
confidence: 81%
“…Several reports showed that PEG- IFN exhibited a strong anti-tumor effect, and that the combination of PEG-IFN and chemoreagents was effective for the treatment of several cancer types (10,21,22). It was also reported that PEG-IFN had an anti-tumor effect against HCC (11), and our results supported this. In our study, the anti-tumor effect of PEG-IFN was almost the same as that of conventional IFN.…”
Section: Discussionsupporting
confidence: 81%
“…INFs induce apoptosis in hepatoma cells, activate pro-apoptotic PKR [10] and upregulate death receptor ligands. However, antiapoptotic effects have also been described [7,[31][32][33] .…”
Section: Enhanced Hepatocyte Apoptosis In Hcv Infection In Vivomentioning
confidence: 99%
“…Liver diseases, such as viral hepatitis, liver cancer, and alcohol-related and drug-related liver injury, are great challenges for health. Worldwide, there are over 350 million hepatitis virus carriers, and over a million deaths per year (about 10% of all deaths in the adult age range) can be attributed to viral hepatitis, and over a million deaths per year are due to hepatocellular carcinoma [44][45][46][47]. The Human Liver Proteome Project (HLPP) is one of the initiatives launched by the HUPO, and is the first initiative of the human proteome project for human organs/tissues [45].…”
Section: Introductionmentioning
confidence: 99%